UNDERSTANDING LEARNERS’ NEED OF ESP FOR ACCOUNTANCY PROGRAM AT VOCATIONAL SCHOOL - Semi Sukarni (English Review: Journal of English Education, 2020)
The main  objective of Vocational High School (SMK) is  to prepare learners to specific job. At this school, learners are trained the major skills as well as the supportive skills. Language, in this case English, must support the hard skills for the communication at work. However, based on the preliminary research, most teachers use general English as teaching materials. Hence, this study aims to describe the learners‘ target need of learning English at accountancy program at Vocational High School and to identify English skills needed by students of  accountancy program. There were 124 evelenth graders involved in this study which consisted of students of  SMK 2 Purworejo and SMK 1 Wonosobo. To obtain the data, a questionnaire was used. The findings showed that 63.8% of the students want to look for a job after graduated, while 36.2% of them want to continue their study. Further, speaking is the most important skill and vocabulary related to the technical terms are needed by students. Another necessity is the availability of textbook containing ESP materials to support learners to develop their communication skill.